2023
DOI: 10.3389/fnut.2023.1137247
|View full text |Cite
|
Sign up to set email alerts
|

Integrating conservation agriculture with intensive crop diversification in the maize-based organic system: Impact on sustaining food and nutritional security

Abstract: IntroductionDeveloping an intensive sustainable model and feeding a rising population are worldwide challenges. The task is much more daunting in the North Eastern Himalayas, where, low productive maize (Zea mays)maize (Zea mays) fallow is the main production system in the upland. To increase farm productivity, nutritional security, and energy dietary returns while maintaining environmental sustainability and economic viability, short-duration crops must be included in the maize–fallow system.MethodsA field st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The IOFS integrates the management of all the production systems to achieve a sustainable result economically and environmentally (Manhoudt et al, 2002). An increase in system productivity and net returns due to the scientific integration of farming system enterprises, such as livestock, cereals, pulses, and vegetables, with the in situ production of compost or vermicompost by efficient recycling of farm resources was recorded by many workers (Ansari et al, 2017(Ansari et al, , 2023Das et al, 2019;Layek et al, 2020). The sustainable rice-based integrated farming system (IFS) in an irrigated agro-ecosystem reported that the cropping system of rice-pea-okra achieved a higher rice equivalent yield (REY) (17.88 t/ha), greater system productivity, and higher employment than the conventional rice-wheat cropping system (Ansari et al, 2013;Layek et al, 2017).…”
Section: Impact Of the Iofs On System Productivity And Profitabilitymentioning
confidence: 99%
“…The IOFS integrates the management of all the production systems to achieve a sustainable result economically and environmentally (Manhoudt et al, 2002). An increase in system productivity and net returns due to the scientific integration of farming system enterprises, such as livestock, cereals, pulses, and vegetables, with the in situ production of compost or vermicompost by efficient recycling of farm resources was recorded by many workers (Ansari et al, 2017(Ansari et al, , 2023Das et al, 2019;Layek et al, 2020). The sustainable rice-based integrated farming system (IFS) in an irrigated agro-ecosystem reported that the cropping system of rice-pea-okra achieved a higher rice equivalent yield (REY) (17.88 t/ha), greater system productivity, and higher employment than the conventional rice-wheat cropping system (Ansari et al, 2013;Layek et al, 2017).…”
Section: Impact Of the Iofs On System Productivity And Profitabilitymentioning
confidence: 99%
“…Maize, the world's third-largest crop, is of immense agricultural and industrial value. 1,2 The Asian corn borer (Ostrinia furnacalis) is one of the most destructive lepidopteran pests of maize in East Asia and Oceania and poses a significant challenge to control. 3 The larvae of O. furnacalis tunnel into maize plants and feed on stems, branches, flower buds, flowers, and green bolls.…”
Section: Introductionmentioning
confidence: 99%
“…These global issues must be addressed by shifting toward lower energy and more resilient intensive cultivation practices ( 3 , 4 ). For maintaining proper human health and physical wellbeing, the nutritional quality of food is the most important factor ( 5 ). Millets have many nutritional and health benefits ( 6 ) and are considered a superfood ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low-input, resource-efficient crops, such as suitable millets (nutri-cereals), are gaining popularity as prospective solutions for assuring food and nutritional security. Most of the farmers in the region do not use any synthetic fertilizer or pesticides, and hence, they are organic by default ( 5 , 32 , 33 ). The NEHR generates 2.55 million tons of agricultural biomass and has 2.98 million bovines, encouraging organic crop production through recycling for valuable nutrient management inputs ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation